Indicators of Identity and Psychological Well-Being in Immigrant Population - Henríquez, Diego; Urzúa, Alfonso; López-López, Wilson (Frontiers in Psychology, 2021)
Multiple research has indicated that group identity processes are critical to understanding the dynamics of psychological well-being linked to migration. However, few studies have analysed the relationship between identity from different theoretical perspectives, and the mental health of migrants in the Latin American context. Therefore, the purpose of this study was to analyse the relationship between several identity indicators such as ethnic identity, collective self-esteem, identity fusion (with the country of origin and the host country) simultaneously and different dimensions of psychological well-being of Colombian migrants living in Chile. The sample consisted of 887 Colombian migrants, of whom 435 (49%) were men and 452 (51%) were women. Participants were residents of the cities of Arica (n = 204; 23%), Antofagasta (n = 469; 52.9%) and Santiago (n = 214; 24.1%) in Chile. The results revealed by structural equation modelling indicate that collective self-esteem and ethnic identity show positive relationships with almost all dimensions of psychological well-being, while identity fusion with Colombia only showed a positive relationship with the dimension positive relationships and identity fusion with Chile only showed a positive relationship with the dimension autonomy. Implications and limitations of these results are discussed at the end.